Thermal upgrading of manganese ores prior to smelting - Eray, Said (Journal of Mining and Metallurgy, Section B: Metallurgy, 2023)
Ferromanganese smelting in electric arc furnaces is an energy-intensive process with corresponding CO2 emissions and environmental impacts. Upgrading the furnace charge can improve process efficiency and decrease electricity consumption. An oxide manganese ore, consisting mainly of pyrolusite, calcite and goethite, was thermally upgraded by calcination and solid-state reduction. During calcination of the ore at 900-1100°C, carbonates and hydroxides were decomposed and a considerable amount of oxygen was removed. The manganese content of the run-of-mine ore was increased from 39.86% to 47% after calcination. Carbothermic reduction of the ore at 1250°C resulted in almost all of the iron oxide and some of the manganese oxide passing into the metallic form. The results showed that a significant part of the endothermic reactions during the solid-state treatment of the ore can be carried out with low-cost fossil fuels. This leads to enrichment of the electric arc furnace charge, lower electricity consumption in the furnace, lower overall processing costs and a more efficient smelting process.
Keywords: manganese ore; thermal upgrading; calcination; reduction